2017
DOI: 10.1175/jpo-d-17-0071.1
|View full text |Cite
|
Sign up to set email alerts
|

The Transient Response of Ice Shelf Melting to Ocean Change

Abstract: Idealized modeling studies have shown that the melting of ice shelves varies as a quadratic function of ocean temperature. However, this result is the equilibrium response, derived from steady ice-ocean simulations subjected to a fixed ocean forcing. This study considers instead the transient response of melting, using unsteady simulations subjected to forcing conditions that are oscillated with a range of periods. The results show that the residence time of water in the subice cavity offers a critical time sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…As the period of variability decreases below 5 years, we expect delays to become increasingly trivial. This expectation is consistent with Holland (2017), who showed that for small, warm ice shelves (similar to Thwaites Ice Shelf), ocean temperature variability below 5-year periodicity has a complex interaction with subshelf melting that tends to cancel out the effects of warm and cold phases of variability, at least for idealized model configurations. This is because water mass residence times are long enough relative to the period of variability to preclude complete cavity flushing between alternating warm and cold phases.…”
Section: Role Of Variability Periodsupporting
confidence: 90%
“…As the period of variability decreases below 5 years, we expect delays to become increasingly trivial. This expectation is consistent with Holland (2017), who showed that for small, warm ice shelves (similar to Thwaites Ice Shelf), ocean temperature variability below 5-year periodicity has a complex interaction with subshelf melting that tends to cancel out the effects of warm and cold phases of variability, at least for idealized model configurations. This is because water mass residence times are long enough relative to the period of variability to preclude complete cavity flushing between alternating warm and cold phases.…”
Section: Role Of Variability Periodsupporting
confidence: 90%
“…An ice influx of 2 × 10 5 m 2 a −1 per unit width is prescribed at the “southern” boundary with a fixed calving front at 300 km, and no‐slip conditions at the “east”‐“west” boundaries. The “northern” ocean boundary is restored to temperature and salinity profiles representative of conditions observed in the Amundsen Sea (Figure b, De Rydt et al, ; Holland, ). The boundary restoring occurs over a width of 10 km with a time scale increasing linearly from 1 day to 10 days on the inner edge.…”
Section: Methodsmentioning
confidence: 89%
“…Holland () considers the transient response of ice shelf melting to variable ocean forcing. For ocean oscillations slower than the ocean cavity residence time, melting anomalies adhere to the equilibrium response derived from steady simulations and transient ocean history is unimportant.…”
Section: Introductionmentioning
confidence: 99%
“…they do not account for ocean circulation timescales (e.g. water residence time in ice-shelf cavities, Holland, 2017). None of the parameterisations account for the Coriolis effect or for bathymetric features (e.g.…”
Section: Ocean Melting From Ocean-dependent Sub-shelf Parameterisationsmentioning
confidence: 99%